Biomaterials for Interfacing Cell Imaging and Drug Delivery: An Overview - Biswas A.; Shukla A.; Maiti P. (My University, 2025)
This feature article provides an overview of different kinds of futuristic biomaterials which have the potential to be used for fluorescent imaging and drug delivery, often simultaneously. The synthesis route or preparation process, fluorescence property, release profile, biocompatibility, bioimaging, and mechanistic approaches are vividly discussed. These include bioimaging with fluorescently doped quantum dots, mesoporous silica, noble metals, metal clusters, hydrophilic/hydrophobic polymers, semiconducting polymer dots, carbon/graphene dots, dendrimers, fluorescent proteins, and other nanobiomaterials. Another section discusses the controlled and targeted drug, gene, or biologically active material delivery using various vehicles such as micelles, 2D nanomaterials, organic nanoparticles, polymeric nanohybrids, and chemically modified polymers. In the last section, we discuss biomaterials, which can deliver biologically active molecules, and imaging the cell/tissue. © 2019 American Chemical Society.